DEVELOPING ENGLISH MATERIALS FOR THE ELEVENTH GRADE STUDENTS OF SMK TRIATMA JAYA SINGARAJA WITH THE INSERTION OF THE VALUES OF NATION CHARACTER - ., I WAYAN PUTRAWAN; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
This study is a Research and Development study (R&D) which aimed at (1) identifying problem in the existing materials used at SMK Triatma Jaya Singaraja, (2) identifying the needs of the English materials for SMK students, (3) determining the suitable design of the English materials for SMK Students, (4) developing English materials for SMK Students, (5) measuring the effectiveness of the English materials developed, (6) determining the quality of the materials developed. The research was conducted at SMK Pariwisata Triatma Jaya Singaraja in academic year 2012/2013. The subject of the study was the eleventh grade students of Food & Beverage Department. The data of the present study was collected by interview, questionnaire test and document analysis. The instruments used in the present study were interview guide, document analysis worksheet, questionnaire, and rubric. The data of the present study was analyzed descriptively and quantitatively. This present study showed that (1) the problems faced by the existing materials used at SMK Triatma Jaya Singaraja are irrelevancy of the materials with the department of the students, insufficiency of pictures and illustration on the materials, and non-existence of the clear statement of the development of the values of nation character. (2) The need of the English materials for SMK students are the materials must follow the basic competences of the syllabus, the materials must include English expression, text, and grammar focus, reading materials should be quite long, materials discuss kitchen work safety, materials must include earth saving program, materials must discus the technology in kitchen, materials must be equipped with sufficient pictures, and the materials should relate to F & B service. (3) The English material for SMK students are designed to meet the need of school syllabus, teacher, students and tourism industry, should insert the values of nation character, and conform with the criteria of good materials. (4) The materials development model used are the combination of Dick and Carey and Tomlinson Models. The new model consists of five major stages. They are (a) need analysis, (b) drafting, (c) expert judgment, (d) field test, and (e) production. (5) The materials developed were less effective than the old materials. The average score for pre-test was 78.2 and the average score for post-test was 73. It was because of (a) time limitation, (b) length of the text, and (c) students? readiness. (6) The quality of the materials developed is excellent. The final product of this research was the department related and character based English Materials completed with compact disc (CD) for listening material. The materials are in the form of text which consists of two units. keyword : research & development (R&D) and the values of nation character